Interaction Between Conservation Tillage and Nitrogen Fertilization Shapes Prokaryotic and Fungal Diversity at Different Soil Depths: Evidence From a 23-Year Field Experiment in the Mediterranean Area - Piazza, Gaia; Ercoli, Laura; Nuti, Marco; Pellegrino, Elisa (Frontiers in Microbiology, 2019)
Soil biodiversity accomplishes key roles in agro-ecosystem services consisting in preserving and enhancing soil fertility and nutrient cycling, crop productivity and environmental protection. Thus, the improvement of knowledge on the effect of conservation practices, related to tillage and N fertilization, on soil microbial communities is critical to better understand the role and function of microorganisms in regulating agro-ecosystems. In the Mediterranean area, vulnerable to climate change and suffering for management-induced losses of soil fertility, the impact of conservation practices on soil microbial communities is of special interest for building mitigation and adaptation strategies to climate change. A long-term experiment, originally designed to investigate the effect of tillage and N fertilization on crop yield and soil organic carbon, was utilized to understand the effect of these management practices on soil prokaryotic and fungal community diversity. The majority of prokaryotic and fungal taxa were common to all treatments at both soil depths, whereas few bacterial taxa (Cloacimonates, Spirochaetia and Berkelbacteria) and a larger number of fungal taxa (i.e., Coniphoraceae, Debaryomycetaceae, Geastraceae, Cordicypitaceae and Steccherinaceae) were unique to specific management practices. Soil prokaryotic and fungal structure was heavily influenced by the interaction of tillage and N fertilization: the prokaryotic community structure of the fertilized conventional tillage system was remarkably different respect to the unfertilized conservation and conventional systems in the surface layer. In addition, the effect of N fertilization in shaping the fungal community structure of the surface layer was higher under conservation tillage systems than under conventional tillage systems. Soil microbial community was shaped by soil depth irrespective of the effect of plowing and N addition. Finally, chemical and enzymatic parameters of soil and crop yields were significantly related to fungal community structure along the soil profile. The findings of this study gave new insights on the identification of management practices supporting and suppressing beneficial and detrimental taxa, respectively. This highlights the importance of managing soil microbial diversity through agro-ecological intensified systems in the Mediterranean area.